Wetting Characteristics of Al-containing Sn-1Ag-0.5Cu Solder Alloy on Cu Substrate using Wetting Balance and Spread area Methods. (2015) - Sabri, Mohd Faizul Mohd; Said, Suhana Binti Mohd; Shnawah, Dhafer Abdulameer
Abstract: In this work, we investigate the effects of 0.1 and 0.5 wt.% Al additions on the wettability of Sn-1Ag-0.5Cu solder on a Cu substrate. Spread area and wetting balance methods were used to evaluate the wettability of the solders. The results of both tests show that the addition of 0.1 wt.% Al does slightly improve the wetting properties of the Sn-1Ag-0.5Cu solder, whereas the addition of 0.5 wt.% Al worsens the wetting properties.